A comprehensive review on the use of sugarcane bagasse ash as a supplementary cementitious material to produce eco-friendly concretes. (2022) - Saad Agwa, Ibrahim; Zeyad, Abdullah M.; Tayeh, Bassam A.; Adesina, Adeyemi; de Azevedo, Afonso R.G.; Amin, Mohamed; Hadzima-Nyarko, Marijana
Abstract: The growing interest in finding partial substitutes for cement is the result of the desire to reduce air pollution caused by the cement industry. One of these partial substitutes is sugarcane bagasse (SCB). SCB is a by-product of the sugar industry extracted from sugarcane. After burning, a large volume of SCB becomes sugarcane bagasse ash (SCBA) to generate electricity during sugar processing. Many papers studied the SCBA influences as a construction material due to having pozzolanic characteristics. This paper is a comprehensive review of the SCBA used as a supplementary cementitious material (SCMs) to produce eco-friendly concretes. Firstly, treatment, physical and chemical properties of SCBA. Finally, review the concrete properties, including SCBA. The concrete properties such as slump, mechanical properties, water absorption, porosity, and microstructure. Based on the literature review, the slump increases or decreases with increasing the SCBA percentage because of influenced treatment by heating and/or milling, and optimum replacement ratio range of 5%–10% better mechanical properties.